Applying imaging mass spectrometry to define the N-glycan profiles of co-localized virus and immune cell infiltrates in post-COVID-19 infected lung autopsy tissues - Jones, E. Ellen; Drake, Richard R.; Dressman, James W.; Parihar, Vaunita; Stubler, Rachel; Masters, Elysia; Mercer, Kelly E. (Frontiers in Analytical Science, 2022)
The current COVID-19 pandemic is characterized by a broad range of disease severity in patients. This diversity in clinical manifestations has complicated our understanding of the SARS-CoV-2 pathogenesis and highlights the significance of an individual’s ability to mount an effective viral immune response. Glycosylation is a common post-translational modification occurring in complex organisms and is imperative for immune cell function. In this study, a combination approach with immunohistochemistry (IHC) and matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) was utilized to determine the spatial distribution of N-glycans and immune cell populations in COVID-19 lung tissues. Tissues from seven SARS-CoV-2, PCR + donors were analyzed. Tissues represented a spectrum of time spent on ventilators which was reflected in their respective viral infection status and lung pathologies. N-glycan distributions in the MALDI-IMS images were then correlated with H&E staining and IHC of SARS-CoV-2 spike protein, CD4, CD8, CD163 and CD11b. Distinct and shared N-glycan signatures were identified in association with specific immune cell types, and their co-localization with the viral spike protein. Additionally, we observed unique patterns of α2,3-linked and α2,6-linked sialic acid glycans that associated with both immune cell populations and fibrotic regions within the tissue architecture. N-glycan MALDI-IMS is an effective tool to further understand tissue-localized immune cell populations in response to emerging viral pathogens such as SARS-CoV-2.